Marketing Mix and Role of 4A’ In Marketing Mix: Evolution and Importance of Marketing Mix in Modern Times (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Theterm "marketing-mix"was first coined by Neil Borden, the president of the American Marketing Association in1953. It is still used today to make important decisions that lead to theexecution of a marketing plan. The various approaches that are usedhave evolved over time, especially with the increased use of technology.